Biased Opioid Receptor Ligands: Gain without Pain. (April 2017) - Ranjan, Ravi; Pandey, Shubhi; Shukla, Arun K.
Abstract : Kappa opioid receptor (κ-OR) agonists are promising therapeutic candidates for pain and itch; however, they also exhibit the adverse effects of sedation and dysphoria. A recent study has demonstrated that a G protein-biased agonist for κ-OR provides effective pain and itch relief without causing sedation or dysphoria, in animal models.